(untitled) (International Journal of Physiotherapy, 2017)
Background: The trunk plays a vital role in limb excursion and manipulation. Hence core muscle strength invariably affects the performance of the upper extremity skills. Thus this study tried to determine the correlation between core muscle strength and hand-eye coordination in non-athletes with low back pain. Methods: 20 nonathletic subjects with low back pain were selected based on the selection criteria. Day 1 core muscle strength was assessed using Plank Test and Sorensen Test. Day 2 hand-eye coordination was assessed using Alternate Wall Toss Test and Simultaneous Ball Throw Test. A rest period of 2 hours was given between both the tests. Results: Pearson’s Correlation analysis was doe to find the relationship between the scales. The correlation analysis of plank test and AWT reveled r = 0.8 with significant difference (p <0.003). The analysis of plank test and SBT revealed r=0.7 with significant difference (p <0.011). The correlation analysis of Sorensen test and AWT revealed r= 0.8 with significant difference (p <0.008). The analysis of Sorensen Test and SBT revealed r=0.7 with significant difference (p<0.005). Conclusion: This study concludes that there is a strong positive correlation between the Core Muscle Strength and Hand-Eye Coordination in nonathletes with Low Back Pain